Upaya Pencegahan dan Penanggulangan Tindak Pidana Narkotika Serta Obat-obat Terlarang di Daerah Terpencil & Berkonflik - Ahmad Fanani Eko Prasetya; Erwin Owan Hermansyah; Dwi Atmoko (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
The existence of the police as the front guard in enforcing criminal law has been guaranteed by Law Number 2 of 2002 concerning the Police of the Republic of Indonesia which places the position of the police as a government institution which has the main task of enforcing the law, maintaining security and public order, as well as providing protection. protection and service to the community. In carrying out these main tasks, the police institution requires police functions that have their respective work areas which are interrelated and integrated. Law Number 2002 concerning the Indonesian National Police, dogmatically normatively, has regulated the functions of the Indonesian police, namely precisely in Article 2 that the function of the police is to carry out one of the functions of state government in law enforcement duties in addition to protection, protection and community service. Through the function of criminal law enforcement, it is of course included in the framework for dealing with drug crimes. The reality of illegal drug trafficking and distribution on remote or coastal islands is of course a type of criminal act that must be addressed as early as possible, so that it does not have a widespread impact on public order and security. Problems of distribution and abuse of Narcotics and illegal drugs (abbreviated as Narkoba). Especially in remote and especially conflict-ridden areas, it turns out that it has entered an alarming stage that must be handled seriously, because this could cause damage to the nation's roots in those areas. This is where awareness of the illegal distribution of drugs is needed, which should be increased from an early age. In this regard, the role of the police, especially in remote areas, for example in the interior or on the borders of islands in Indonesia, requires coordination between the roles of the government, police and local communities on these islands in synergy to tackle and prevent the distribution of narcotics and drugs